The sea wolf eaudiobook - London, Jack (Recorded Books Inc., 1988)
Generations have been spellbound by this harrowing story of danger on the sea, psychological confrontation, and the dual nature of mankind. Humphrey Van Weyden, a San Francisco sophisticate, finds himself the captive voyager aboard the Ghost, captained by the brutal and barbaric Wolf Larsen. An excerpt: "And where am I?" I asked Johnson, whom I took, and rightly, to be one of the sailors. "What vessel is this, and where is she bound?" "Off the Farallones, heading about sou-west," he answered, slowly and methodically, as though groping for his best English, and rigidly observing the order of my queries. "The schooner Ghost, bound seal-hunting to Japan." "And who is the captain? I must see him as soon as I am dressed." Johnson looked puzzled and embarrassed. He hesitated while he groped in his vocabulary and framed a complete answer. "The cap'n is Wolf Larsen, or so men call him. I never heard his other name. But you better speak soft with him. He is mad this morning. The mate—" But he did not finish. The cook had glided in. "Better sling yer 'ook out of 'ere, Yonson," he said. "The old man'll be wantin' yer on deck, an' this ayn't no d'y to fall foul of 'im." Johnson turned obediently to the door, at the same time, over the cook's shoulder, favouring me with an amazingly solemn and portentous wink as though to emphasize his interrupted remark and the need for me to be soft-spoken with the captain..